The world without us - Weisman, Alan.; Grupper, Adam. (New York : Audio Renaissance, 2007)
A study of what would happen to Earth if the human presence was removed examines our legacy for the planet, from the objects that would vanish without human intervention to those that would become long-lasting remnants of humankind.
Compact discs.
Unabridged.
Read by Adam Grupper.
Keywords: Nature -- Effect of human beings on; Material culture; Human-plant relationships; Human-animal relationships; Audiobooks